Sequencing and mutations analysis of the first recorded SARS-CoV-2 Omicron variant during the fourth wave of pandemic in Iraq - Ahmed,Jivan Qasim (2022)
Abstract Despite vaccine development and vaccination programs underway around the globe, the coronavirus disease 2019 (COVID-19) pandemic has not been controlled as the SARS-CoV-2 virus is evolving and new variants are emerging. This study was conducted to sequence and molecularly characterize the representing samples from the early fourth SARS-CoV-2 wave in Iraq. Here, we have performed next-generation sequencing of whole-genome sequencing of two representing samples from the country's early beginning of the fourth pandemic wave. The samples were sequenced using Illumina Miseq system, and the reference sequences were retrieved from GISAID database. Phylogenetic analysis was performed through Mega software. This study provides an initial sequence analysis and molecular characterization of the first Omicron variant cases recorded in the country. Our analysis revealed many mutations on the spike glycoprotein, especially on the receptor binding domain, with potential impact on immune escape and infectivity. The study findings suggest considering the highly mutated immunogenic epitope of the Omicron variant as a reference for developing a new vaccine for combating the ongoing pandemic.